KAJIAN KERUANGAN LAYANAN PASAR DI KABUPATEN TAPANULI UTARA - , Susy Magdalena Silaban, Ir. Gunung Radjiman, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to describe the characteristic of market service and to find out the markets hierarchy in North Tapanuli Regency. The method used in this study was a qualitative deductive with descriptive approach. Data gathered from interviews, field observations, literature study and secondary data. This study found that the location of market in North Tapanuli Regency is located at central administrative of the subdistrict and formed naturally. A considerable accessibilityâs villages away to the market is not accede with the accessibility standard and the avaibility of transportation facilities is limited. Market with located at national road become bigger market than the market located at regency road. Numeral of variety, amount of goods and market physical is one of the reason for consumer movements happened in the market. Market with more seller movements, variety and volume of goods made the market bigger than the market with fewer. In this context that Tarutung and Siborongborong markets are market hierarchy I, Pahae Julu market, Sipahutar market, Pangaribuan market are market hierarchy II, and Muara market, Pagaran market, Parmonangan market, Adiankoting market, Pahae Jae market, Purbatua market, Garoga market, Simangumban market are market hierarchy III. This study recommends that in order to improve the existing markets it should be supported by better quality of road and transportation from the villages.